Delayed hypersensitivity reaction after hyaluronic acid filler (VCY-20) (Dermatology Reports, 2023)
Hyaluronic acid (HA) filler, a transient injectable used for rejuvenating facial treatments, has become increasingly popular over time since it doesn’t require surgery. Although these procedures are generally safe, there are some application-related complications. These issues fall into three categories: reactions with early, delayed, or late onset. This case report features a 55-yearold female patient who developed widespread facial edema as a result of a delayed hypersensitivity reaction that happened after HA filler was applied.